O projeto Picar o Ponto: Memórias orais de operários da Fábrica Robinson - Célia Gonçalves Tavares; Roberto Leite (Midas: Museus e Estudos Interdisciplinares)
Picar o ponto (Clocking in, reference to the beginning of a shift in a factory by inserting an individual card in a clock-like device), a gesture repeated by the workers every day, appeared as an obvious title when the Robinson Foundation team decided to conceive an activity to keep alive the link with the workers of Robinson Factory, whose doors closed in early 2009. In Picar o ponto the factory worker returns to the factory and brings along the necessary items to tell the story of his or her time at the factory: objects, photographs, documents… or just memories. Integrated within the Robinson Museum programme Dia 17 Acontece, the aim is to create room for exchanging personal experiences through biographical accounts. The intention of this initiative is to bring citizens closer to the factory, alerting them to the importance of industrial heritage, interweaving the approaches of experts from various areas of cultural heritage and those of past factory workers in the same space and time. A record of personal participation, the activity seeks to strengthen ties with former workers as key players of the memory of the Robinson Factory and as essential elements in building the Robinson space in Portalegre, a Portuguese city in Northern Alentejo with a strong industrial tradition.